The budget impact of brodalumab for the treatment of moderate-to-severe plaque psoriasis on US commercial health plans. (4th May 2018) - Feldman, Steven R.; Wu, Jashin J.; Rastogi, Shipra; Menges, Brandy; Lingohr-Smith, Melissa; Lin, Jay
Abstract: Introduction: Brodalumab is a new biologic approved by the US Food and Drug Administration in 2017 for the treatment of moderate-severe psoriasis. This study evaluated the impact of the introduction of brodalumab on the pharmacy budget on US commercial health plans. Methods: An Excel-based health economic decision analytic model with a US health plan perspective was developed. The model incorporated published moderate-to-severe psoriasis prevalence data; market shares of common biologic drugs, including adalimumab, ustekinumab, secukinumab, ixekizumab, and etanercept, used for the treatment of moderate–severe psoriasis; 2017-year Wholesale Acquisition Costs for the biologic drugs; drug dispensing fee; patient co-pay; and drug contracting discount. Total annual health plan costs for the biologic drugs were estimated. Scenarios with different proportions of patients treated with brodalumab were compared to a control scenario when no brodalumab was used. Results: In a hypothetical commercial health plan covering two million members, 7, 038 moderate-to-severe psoriasis patients were estimated to be eligible for treatment with brodalumab. Prior to brodalumab approval, the proportions of patients treated by other biologics were estimated at 50.8% for adalimumab, 13.5% for ustekinumab, 14.1% for secukinumab, 4.4% for ixekizumab, and 17.2% for etanercept. With a 20% drug price discount applied to all biologics, the annual health plan costs for brodalumab, adalimumab, ustekinumab, secukinumab, ixekizumab, and etanercept were estimated at $37, 224, $49, 166, $55, 084, $56, 061, $64, 396, and $57, 170, respectively. When no brodalumab is used, the total annual pharmacy budget for the biologics used among these patients was estimated at $414, 362, 647. Among scenarios where the proportions of brodalumab usage were 3%, 8%, 16%, and 30%, the total annual pharmacy cost was estimated to be reduced by $3, 698, 129, $9, 861, 677, $19, 723, 355, and $36, 981, 290, respectively. Conclusion: Based on the economic model, brodalumab has the potential to substantially reduce pharmacy expenditures for the treatment of patients with moderate-to-severe plaque psoriasis in the US.